Analysis of Roll on/Roll off (RORO) Ship Strategy in Supporting Marine Transportation Infrastructure using the SWOT Method - Sugiharto, Hendrik; Sulistyo, Juny Andry; Sumirin, Sumirin (ASTONJADRO, 2026)
Indonesia, as an archipelagic country, places maritime transportation as the backbone of interregional connectivity. Roll-On/Roll-Off (RO-RO) vessels are a strategic mode of transportation due to their loading and unloading efficiency and flexibility. However, implementation at Sampit Port is still hampered by limited docks, load imbalances, and high operational costs. This article aims to review the literature related to RO-RO vessel development strategies using a SWOT analysis approach enriched with IFE/EFE and QSPM matrices. The research method uses a literature-based review by examining journals, institutional reports, and regulations related to maritime transportation. The analysis is carried out in three stages: (i) identification of internal-external factors within the SWOT framework, (ii) evaluation of factor weights using IFE/EFE, and (iii) prioritization of strategies using QSPM. Performance indicators such as Turnaround Time (TAT), Load Factor, and On-Time Performance (OTP) are used to assess operational effectiveness. The study results indicate that Sampit Port is in the WO (Weakness-Opportunity) quadrant, indicating that internal weaknesses can be addressed through external opportunities, particularly the maritime toll policy and logistics digitalization. The emerging priority strategies are the construction of a dedicated RO-RO dock and the implementation of digital systems for cargo management and service scheduling. In conclusion, improving RO-RO performance in Sampit requires synergy between operators, the government, and other stakeholders. This article contributes to the academic literature on SWOT-IFE/EFE-QSPM, provides practical recommendations for PT Dharma Lautan Utama, and emphasizes the urgency of a dedicated dock development policy and the integration of logistics digitalization.